2016
DOI: 10.1371/journal.pone.0162956
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary Flavones as Dual Inhibitors of DNA Methyltransferases and Histone Methyltransferases

Abstract: Methylation of DNA and histone proteins are mutually involved in the epigenetic regulation of gene expression mediated by DNA methyltransferases (DNMTs) and histone methyltransferases (HMTs). DNMTs methylate cytosine residues within gene promoters, whereas HMTs catalyze the transfer of methyl groups to lysine and arginine residues of histone proteins, thus causing chromatin condensation and transcriptional repression, which play an important role in the pathogenesis of cancer. The potential reversibility of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 55 publications
5
34
0
Order By: Relevance
“…Previous reports have demonstrated that LUT can inhibit DNMT enzyme activity and reverse the CpG hypermethylation of DNA. 35 In our study, hypermethylation of the three CpGs (59.2% methylation) was observed in HCT116 cells without LUT treatment. Treatment with a combination of 5-Aza and TSA, a positive control of demethylation, significantly decreased the CpG methylation level to 41%.…”
Section: Lut Reduced the Cpg Methylation Of The Nrf2 Gene Promoter supporting
confidence: 48%
“…Previous reports have demonstrated that LUT can inhibit DNMT enzyme activity and reverse the CpG hypermethylation of DNA. 35 In our study, hypermethylation of the three CpGs (59.2% methylation) was observed in HCT116 cells without LUT treatment. Treatment with a combination of 5-Aza and TSA, a positive control of demethylation, significantly decreased the CpG methylation level to 41%.…”
Section: Lut Reduced the Cpg Methylation Of The Nrf2 Gene Promoter supporting
confidence: 48%
“…As such, apigenin acts on HDAC1 and HDAC3 and increases the global histone acetylation and the localized hyperacetylation of histone H3 on the p21/Waf1 promoter [132]. A study by Kanwal et al [133] demonstrated that apigenin could also function as a dual epigenetic inhibitor having ability to alter the DNA methyltransferase and histone deacetylase activity. It does so by reversing both DNA methylation and the trimethylation of lysine 27 at the H3 histone in cultured cells and in an artificial in vitro system [133].…”
Section: 0 Effect Of Apigenin In Various Human Cancersmentioning
confidence: 99%
“…A study by Kanwal et al [133] demonstrated that apigenin could also function as a dual epigenetic inhibitor having ability to alter the DNA methyltransferase and histone deacetylase activity. It does so by reversing both DNA methylation and the trimethylation of lysine 27 at the H3 histone in cultured cells and in an artificial in vitro system [133]. This study further supported an investigation on apigenin and its role as a chemopreventive agent.…”
Section: 0 Effect Of Apigenin In Various Human Cancersmentioning
confidence: 99%
“…However, HDACs and DNMTs are also essential for the downstream maintenance of chromatin structure in the steady-state, hence non-selective inhibition of these enzymes can induce serious adverse effects that disrupt normal cell function1718. Recently, dietary phytochemicals such as indicaxanthin (Ind), genistein, and several flavones such as apigenin, chrysin, and luteolin, have been reported to decrease DNA methylation level by inhibiting DNMT activities192021. Interestingly, these flavones and Ind showed a direct interaction with DNMTs, which assessed by molecular modeling, showed possibility as good alternatives instead of chemically synthesized DNMT inhibitors2021.…”
mentioning
confidence: 99%
“…Recently, dietary phytochemicals such as indicaxanthin (Ind), genistein, and several flavones such as apigenin, chrysin, and luteolin, have been reported to decrease DNA methylation level by inhibiting DNMT activities192021. Interestingly, these flavones and Ind showed a direct interaction with DNMTs, which assessed by molecular modeling, showed possibility as good alternatives instead of chemically synthesized DNMT inhibitors2021. Therefore, a more promising approach could be to identify how dietary intake of bioactive phytochemicals can promote and maintain ‘anti-tumor’ epigenetic profiles in the consumer, potentially leading to low-cost dietary interventions that protect a large fraction of the global population against cancers.…”
mentioning
confidence: 99%